Tilapia introduction in China: Economic boom in aquaculture versus ecological threats to ecosystems - Wen Xiong; Chuanbo Guo; Rodolphe E. Gozlan; Jiashou Liu (Reviews in Aquaculture, 2023)
The introduction and use of non‐native species in aquaculture have played a central role in the development of this economic sector worldwide. Tilapia is one of the most widely introduced species in the world, and China has become the largest producer and consumer of tilapia. While non‐native tilapia in China support provisioning ecosystem services of substantial economic value, the invasion also poses potential threats to native fish diversity, ecosystems and ultimately the sustainable fisheries development. However, knowledge regarding the invading pathway, aquaculture development, economic benefits and the ecological impacts of such important non‐native species is still limited, especially in China. Based on thorough literature review as well as field surveys, this paper has comprehensively presented the introduction of tilapia species across a range of aquatic habitats and its role in the aquaculture industry growth, emphasising the economic benefits in China. In addition, we also synthesised the potential negative ecological impacts caused by tilapia invasion with global evidences, which will provide excellent lessons and management recommendations for China and other countries worldwide. Future trends tend to indicate an increase in the number and frequency of tilapia's introduction in China, with an increasing likelihood of environmental impacts. However, it is apparent that the aquaculture of non‐native tilapias is a highly profitable activity in China which makes the introductions inevitable, therefore, alternative management strategies and implications are further discussed to seek to achieve more sustainable and ecosystem‐friendly aquaculture, reduce the risks and negative impacts on ecosystems while still maintaining the economic benefits.